This week, I have learned how to find the x intercept from a quadratic formula.

At the beginning, I was very surprised since the step it took was very simple and understandable.

From y= to y= (x+2)(x+6), this was using factoring!!!

Since to find x intercept needed factoring, it was very easy.

Let’s begin.

As I mentioned before, it is factoring.

The equation, y=a(x-x1)(x-x2), x1 is your first x intercept and the x2 is your second x intercept. Now lets use an example and see how will we find the x intercept.

For example

y= to y= (x+2)(x+6)

In this case, first x1= -2 and x2= -6.

I have said negative 2 and negative 6 since in the equation (x-x1) there is a subtraction which means negative. As a result it will become a negative.